THE ROLE OF MUSEUM BUILDING IN THE DEVELOPMENT OF TOURISM IN CMW - Olga Alexandrovna Kartasheva; Natalia Yurievna Klimova (Современная наука и инновации)
The article reveals the main stages of origin and development of the most known museums located in the region of Caucasian Mineral Waters. It describes how the creation of the museums helps to analyze the role of scientists and art, as well as the public of resort towns in preservation of history and culture of the region. The special attention is paid to the open-air museum, the first in the Caucasian Mineral Waters region- the Museum of Antiquities of the North Caucasus.